Humoral detection of leukaemia-associated antigens in presentation acute myeloid leukaemia. - Guinn, B; Bland, E; Lodi, U; Liggins, A; Tobal, K; Petters, S; Wells, J; Banham, A; Mufti, G (2005)
The serological analysis of recombinant cDNA expression libraries (SEREX) technique was used to immunoscreen a testes cDNA expression library with sera from newly diagnosed acute myeloid leukaemia (AML) patients. We used a testis cDNA library to aid our identification of cancer-testis (CT) antigens. We identified 44 antigens which we further immunoscreened with sera from AML, chronic myeloid leukaemia (CML), and normal donors. Eight antigens were solely recognised by patient sera including the recently described CT antigen, PASD1, and the cancer-related SSX2 interacting protein, SSX2IP. RT-PCR analysis indicated that we had identified three antigens which were expressed in patient bone marrow (BM) and peripheral blood (PB) but not in normal donor samples (PASD1, SSX2IP, and GRINL1A). Real-time PCR (RQ-PCR) confirmed the restricted expression of PASD1 in normal donor organs. Antigen presentation assays using monocyte-derived dendritic cells (mo-DCs) showed that PASD1 could stimulate autologous T-cell responses, suggesting that PASD1 could be a promising target for future immunotherapy clinical trials.